Plant Effectiveness of Acorus calamus, Pistia stratiotes, Azolla pinnata as Hyperaccumulator Candidate of Phytoremediation Agent for Copper (Cu) Absorption - Dewi, Juriyah Astika; Nurwahyuni, Isnaini; Munir, Erman (Universitas Labuhanbatu, 2023)
Metals are harmful pollutants because they cannot be broken down by living organisms. An excess of metal can become toxic. The metal in question is copper (Cu). This research aimed to determine the phytoremediation effectiveness of Acorus calamus, Pistia stratiotes, and Azolla pinnata as candidates for Cu metal absorption. This investigation employed a wholly random factorial design with two factors: plant absorbent materials comprised of three plant species (Acorus calamus, Pistia stratiotes, and Azolla pinnata) and absorption concentrations of 2 and 5 ppm. The ANOVA test was used to analyze the data, followed by the average difference test. According to the results of this study, three plants—Acorus calamus, Pistia stratiotes, and Azolla pinnata—are capable of reducing Cu metal in water. The Acorus calamus plant can reduce Cu concentrations in water from 2 ppm to 96.85% and from 5 ppm to 96.80%. Pistia stratiotes plants can reduce Cu level in water from 2 ppm to 96.50% and 5 ppm to 99.94% at concentrations of 2 and 5 ppm, respectively. The Azolla pinnata plant can reduce Cu level in water from 2 ppm to 98.50% and from 5 ppm to 96.54% at concentrations of 2 ppm and 5 ppm, respectively. The highest BCF value at a concentration of 2 ppm is in the roots of Azolla pinnata plants, at 6.77 mg/kg, followed by the leaves, at 8.88 mg/kg. The maximum BCF value at a concentration of 5 ppm for Pistia stratiotes plants is 2.26 mg/kg for the roots and 2.46 mg/kg for the foliage. The greatest concentration of TF at 2 ppm in Azolla pinnata is 1.31 mg/kg, while the maximum concentration at 5 ppm in Acorus calamus is 1.98 mg/kg